THE COMPOSITION OF CARBOHYDRATE AND FAT CONSUMPTION AMONG OBESE ADOLESCENTS IN SURABAYA AND SIDOARJO - Christine Florens; Nur Aisiyah Widjaja; Roedi Irawan; Meta Herdiana Hanindita (Media Gizi Indonesia, 2022)
Carbohydrates and fats are macronutrients that have been the most influential factors to obesity. The excess of consumed carbohydrates or fats will be stored as triglycerides in adipocytes. This study aims to analyze the proportion of carbohydrates and fats consumption among obese adolescents from Surabaya and Sidoarjo. This study also revealed the relationship between the proportion with the total calories consumption and body mass index (BMI). This cross-sectional study involved obese adolescents aged 13-18 years old from several junior and senior high schools, conducted during May-September 2020. The subject was selected using a total population sampling method that met inclusion and exclusion criteria. Anthropometries (weight and height) were measured to calculate BMI and determine obesity according to CDC 2000 criteria. A 24-hour-food-recall for the last two days was used to get the dietary information. This study divided carbohydrates consumption into three groups (high (HC), moderate (MC), low(LC)) and fats consumption into two groups (high fats (HF) and non-high fats (Non-HF)). There were 240 obese adolescents participating in this study; 40.4% of them consuming high carbohydrates and 17.5% of them consuming HF on their diets. Although there were several distinctions in carbohydrates and fats composition on diet, the total calorie and the mean BMI were not considerably different based on macronutrients consumption. In conclusion, there were two types of imbalance proportion of macronutrients consumption among our participants, high–carbohydrates-low-fats diet and low-carbohydrates-high-fats-diet.